2013
DOI: 10.1111/tid.12122
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Trypanosoma cruzi in kidney transplant donors and recipients in Mexico City

Abstract: Infectious diseases are common causes of morbidity and mortality among kidney transplant recipients. Chagas disease (CD) has been recognized as an emerging infectious complication of transplantation caused by the parasite Trypanosoma cruzi. CD is prevalent in Mexico, particularly in the southern coastal region. The impact on Mexican kidney transplant programs has not been previously studied prospectively. From 2009 through 2010, serum samples from 59 kidney transplant donors and 405 renal transplant recipients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In Southern California, a 0.3% prevalence was reported from 2002 to 2004. In the Los Angeles County blood bank, confirmed seroreactivity for T. cruzi was found to be 0.1% [21][22][23][24] . In most Brazilian states, death from TBI is decreasing while death from stroke is increasing among deceased donors 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In Southern California, a 0.3% prevalence was reported from 2002 to 2004. In the Los Angeles County blood bank, confirmed seroreactivity for T. cruzi was found to be 0.1% [21][22][23][24] . In most Brazilian states, death from TBI is decreasing while death from stroke is increasing among deceased donors 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of Chagas disease in these studies ranged from 0% to 10.7% depending on the country where the study was performed, the study period, and the serological test used for the diagnosis. 7,[18][19][20][21] Although our study is performed in a Data are reported as number (%) of patients or median (range). * These two patients were born in Spain, but they lived for more than 1 year in Venezuela and Mexico, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9]11 Some Brazilian studies have shown higher risk of Chagas disease reactivation in heart transplant recipients receiving mycophenolate mofetil as a part of the immunosuppression protocol. Therefore, it is recommended not to use mycophenolate mofetil (or at least use reduced doses) in 18 Riarte, 1999 7 Boin, 2010 19 Fitzpatrick, 2010 20 Rodríguez-Romo, 2013 21 Salvador, 2018 1975-1986 1989-1996 1997-2007 2006-2008 2009- Chagas disease patients receiving heart transplantation. 28,29 Nevertheless, no information in other organ transplantations is available.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiology of Chagas Disease in Mexico is still poorly understood, but a recent systematic review of surveys from 2006 to 2017 estimated seroprevalence of T. cruzi infection of 3.38%, corresponding to 4.06 million cases (Arnal et al ., 2019). Although T. cruzi transmission in humans may occur by the congenital transmission (Buekens et al ., 2018), transfusions (Escamilla‐Guerrero et al ., 2012) and organ transplants (Rodríguez‐Romo et al ., 2013), the most common route is by contact with contaminated faeces or urine of Triatomine bugs (Ramsey et al ., 2000; Pizano & Gascón, 2015). Currently, in Mexico seven genera and 31 species have been recorded, of which 19 species are the most abundant as well as the epidemiologically relevant vectors of T. cruzi (Ramsey et al ., 2015) and 11 species are part of the most important complex in that country, the Phyllosoma complex.…”
Section: Introductionmentioning
confidence: 99%